Numerical simulation of double diffusive mixed convective nanofluid flow and entropy generation in a square porous enclosure. (July 2018) - Hussain, S.; Mehmood, K.; Sagheer, M.; Yamin, M.
Graphical abstract: Highlights: An increase is observed in entropy due to heat transfer with a growth in Ri, φ, Da and ∊ . A decrease is noticed in entropy due to heat transfer with a rise in q, Kr and Le . The average Nusselt number increases with a rise in Ri, φ, Da and ∊ . The average Nusselt number decreases with a rise in q, Kr and Le . The average Sherwood number grows with an increase in Ri, Da, q, Kr and Le . Abstract: In the present work, the numerical analysis of a double diffusive mixed convective alumina-water nanofluid flow in a square porous lid driven cavity is investigated to determine the influence of different physical parameters on the heat transfer and entropy generation. The upper wall of the enclosure is moving to the right while all the other walls are at rest. The flow is generated due to the motion of the top wall and the buoyancy forces that are produced due to the difference in temperature. A monolithic Galerkin finite element approach together with geometric multigrid technique has been adopted to solve governing equations for various governing parameters. Analysis has been shown in the form of streamlines, isotherms and isoconcentration, tables and plots. The influence of various physical parameters on the flow, in specific ranges such as the Richardson number ( 0.01 ⩽ Ri ⩽ 5 ), Darcy number ( 0.00001 ⩽ Da ⩽ 0.01 ), porosity parameter ( 0.2 ⩽ ∊ ⩽ 0.8 ), Lewis number ( 0.1 ⩽ Le ⩽ 7 ), buoyancy ratio parameter ( - 2 ⩽ Br ⩽ 2 ), heat generation/absorption parameter ( - 0.4 ⩽ q ⩽ 0.4 ), chemical reaction parameter ( 0 ⩽ Kr ⩽ 0.04 ) as well as the nanoparticles volume fraction ( 0 ⩽ ϕ ⩽ 0.04 ) are investigated and findings are very closely comparable to the previous analysis for the special cases in the literature.